A 3D Co–CN framework as a high performance electrocatalyst for the hydrogen evolution reaction. Issue 48 (27th April 2016) - Chen, Jie; Zhou, Haifeng; Huang, Yongjun; Yu, Huiwu; Huang, Fuying; Zheng, Fengying; Li, Shunxing
Abstract : A 3D Co–CN framework was synthesized with the Co–CN electrode showing exceptionally high catalytic activity and good durability. Only requiring overpotentials of 181 mV and 266 mV to afford current densities of 10 mA cm −2 in acid and alkaline electrolytes, respectively. Abstract : A 3D Co–CN framework was synthesized via a sample annealing route at 600 °C using ZIF-67 as the template. When the 3D framework was applied as a hydrogen evolution cathode, the Co–CN electrode shows exceptionally high catalytic activity and good durability, and it only requires overpotentials of 181 mV and 266 mV to afford current densities of 10 mA cm −2 in acid (0.5 M H2 SO4 ) and alkaline (0.1 M KOH) electrolytes respectively.